Formulation and Evaluation of Niosomal Gel Loaded with Asparagus racemosus Extract for Anti-inflammatory Activity - Hegdekar, Nikhilkumar Yeshwanth; Priya, Sneh; Shetty, Suchith S; Jyothi, Divya (Indian Journal of Pharmaceutical Education and Research, 2023)
Background/Aim: Inflammation typically occurs when infectious microorganisms enter the body, settle in specific tissues, and/or circulate in the blood. Asparagus racemosus extract contains various saponins and flavonoids and plant-origin drugs have fewer side effects and toxicity. The phytoconstituents have less permeability through the skin; to enhance their permeability and effectiveness it was loaded in niosomes. Therefore, the study aimed to formulate and characterize the niosomal gel loaded with Asparagus racemosus extract for anti-inflammatory activity. Materials and Methods: The niosomes containing saponins in the extract were prepared using thin film hydration method and 2³ full factorial design was employed to assess the influence of independent variables span 60 and cholesterol on vesicle size, PDI, zeta potential, and percentage entrapment efficiency. 10% of niosomal and conventional gels were prepared by incorporating optimized niosomes and extract containing total saponin in 1% carbopol gel. Ex vivo permeability studies of prepared gels were performed through goat skin using Franz diffusion cell. An anti-inflammatory study was conducted on albino rat. Results: The statistical analysis revealed the significant effect of independent variables on vesicle size, PDI, entrapment efficiency and zeta potential. SEM image shows vesicles are spherical in shape and uniform in size. The niosomal gel provided a significantly higher amount of steady-state flux and permeability coefficient into the skin than conventional gel. The animal model proved that niosomal gel loaded with total saponins in extract showed significant anti-inflammatory compared to the control. Conclusion: It was concluded that the niosomal gel had better efficacy than the conventional gel.
Keywords: Asparagus racemosus; Niosomes; Span 60; Cholesterol; Factorial design; Carbopol 934